Determining sustainable waste management practices in college and university dining services using the theory of planned behavior - Zhou, Ying (Kansas State University, 2010)
Along with increasing environmental challenges and large quantities of energy demand, many have become concerned about the environment and have implemented “Going Green” strategies. As a result, plans for sustainable development are being adopted by governments, institutions, operations, and individual households. Many National Association of College & University Food Service (NACUFS) members may have heard about sustainability, but they may not apply their knowledge to developing practical outcomes and solutions. Very little research has been published that measures how NACUFS members are responding to Sustainable Waste Management (SWM) and to the new Sustainability Guide published by the NACUFS organization in September 2009. The primary purposes of this study were to ascertain what SWM programs have been implemented in college and university foodservices operations and determine how NACUFS members’ attitudes, subjective norms, and barriers affect the implementation of additional SWM programs based on the Theory of Planned Behavior (TPB). A secondary purpose was to identify the differences in intention to implement sustainable waste management programs based on characteristics of the respondents’ age, size of facility, region of the country and if the facility had a sustainable waste management committee. In this study, 2,184 NACUFS members whose e-mail addresses were listed in the NACUFS membership directory were selected as subjects. The data were analyzed using SPSS version 17.0. Multiple linear regression analysis, T-tests, and ANOVA were used to test the hypotheses and research questions. Statistical significance was set at p≤0.05. The total number of responses was 212 resulting in a 13.5% response rate. The majority of respondents had implemented SWM programs that don’t require major resources. NACUFS members had positive attitudes about implementing a SWM program and their superiors, university administrators, and students’ opinions were important others to consider when implementing a SWM program. Whether a college and university foodservice has a sustainability committee was the only demographic that significantly influenced NACUFS members’ intentions to implement a SWM program. Overall, attitude and subjective norms were the only significant predictors of intention to implement a SWM program (p≤.05). Therefore, if NACFUS members have a positive attitude about sustainability, important others around them who agree and there is a sustainability committee within the operation, they are more likely to implement a SWM program. Keywords: Sustainable waste management, TPB, college and university foodservice
Keywords: Sustainable waste management; Sustainability; TPB; NACUFS; Home Economics (0386)